2019
DOI: 10.3390/toxins11010049
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Profiling of Aflatoxin B1-Induced Rats Treated with Lactobacillus casei Shirota

Abstract: Aflatoxin B1 (AFB1) is a ubiquitous carcinogenic food contaminant. Gut microbiota is of vital importance for the host’s health, regrettably, limited studies have reported the effects of xenobiotic toxins towards gut microbiota. Thus, the present study aims to investigate the interactions between AFB1 and the gut microbiota. Besides, an AFB1-binding microorganism, Lactobacillus casei Shirota (Lcs) was tested on its ability to ameliorate the changes on gut microbiota induced by AFB1. The fecal contents of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…A substantial part of the solid foods prepared for babies is at risk for contamination with aflatoxins [53,54]. Food contaminated with aflatoxin B 1 was found to affect the gut and injures the stomach and the intestine [55]. Studies carried out in animal models have shown that aflatoxin B 1 promotes intestinal damages through perturbation of the intestinal barrier and activation of cell apoptosis and cell proliferation [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial part of the solid foods prepared for babies is at risk for contamination with aflatoxins [53,54]. Food contaminated with aflatoxin B 1 was found to affect the gut and injures the stomach and the intestine [55]. Studies carried out in animal models have shown that aflatoxin B 1 promotes intestinal damages through perturbation of the intestinal barrier and activation of cell apoptosis and cell proliferation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Food contaminated with aflatoxin B 1 was found to affect the gut and injures the stomach and the intestine [55]. Studies carried out in animal models have shown that aflatoxin B 1 promotes intestinal damages through perturbation of the intestinal barrier and activation of cell apoptosis and cell proliferation [55]. Saran et al hypothesized that stunted children may fail to grow due to injury as a result of recurrent infections to the gut epithelium leading to impaired gut-mediated immunity, poor nutrient absorption, and poor appetite [56].…”
Section: Discussionmentioning
confidence: 99%
“…Other metabolomics based studies also found that AFB1 disrupted several important metabolic pathways of gut microbiota, including synthesis of SCFAs, pyruvic acid-related pathways, amino acids, bile acids, and long-chain fatty acids metabolism (Zhou et al, 2018b(Zhou et al, , 2019a), suggesting that gut microbial metabolism disruption contributes to the pathogenesis of AFB1-induced diseases. Probiotics supplementation including Lactobacillus Species (Liew et al, 2019;Wacoo et al, 2020), Propionibacterium freudenreichii (El-Nezami et al, 2006), Bacillus subtilis , andCandida utilis (Chang et al, 2020b) exerted protective effects against AFB1 both in animal experiments and human trials. These studies illustrate that AFB1 perturbs gut microbiota which can be restored by probiotics and they also help degrade AFB1 and thus lower toxicity.…”
Section: Substances Other Than Drugsmentioning
confidence: 99%
“…In addition to the human studies, several papers examine the role of mycotoxins in the establishment and/or development of different health effects in animals [21][22][23][24]. Interference of mycotoxins exposure in the gut microbiome and immunity are evaluated in gilts, turkeys, and rats [22][23][24]. In pre-pubertal gilts, a minimal anticipated biological effect level (MABEL) dose of ZEN stimulated the growth of specific strains of intestinal microbiota [22].…”
mentioning
confidence: 99%
“…In turkeys, the effects of aflatoxin B1 (AFB1) on the gastro-intestinal tract are investigated and show that, in addition to the hepatic transcriptome, animal resistance to this mycotoxin occurs in organ systems outside the liver [23]. In rats, and also focusing on the effects of AFB1, the findings suggest that AFB1 can alter the gut microbiota composition and that Lactobacillus casei Shirota can reduce the AFB1-induced dissimilarities in the gut microbiota profile [24]. Hepatoxicity associated with the exposure of piglets to fumonisin B1 (FB1) is also studied [21].…”
mentioning
confidence: 99%